Analysis of blood utilisation efficiency driven by clinical management and hospital heterogeneity - Wang, Feng; Xu, Zhi-guo; Lv, Ke; Fei, Jingxian; Yang, Haiying; Ou, Zequn; Song, Yun; Song, Jingxian; Chen, Yizhu; Wang, Le (Frontiers in Public Health, 2025)
BackgroundBlood is a critical yet scarce medical resource, and improving the efficiency with which it is utilised remains a major global challenge. In 2019, China introduced Quality Control Indicators for Clinical Blood Use in an attempt to standardise management. However, significant discrepancies remain between the intended policy and its practical implementation, resulting in inefficiencies and safety concerns.ObjectiveThis study aims to quantitatively evaluate the impact of administrative policies on clinical blood use, identify the main factors affecting the efficiency with which blood is utilised, and analyse how hospital level and type influence transfusion practices.MethodsA retrospective, multicentre study was conducted using data from 24 secondary and tertiary hospitals in Huzhou between 2020 and 2024. Key quality control indicators and a 25-point transfusion record scoring system were employed. Trends were analysed using ANOVA and chi-square tests, and hospital stratification was analysed using MANOVA. Predictors of blood use per discharged patient were identified using multiple linear regression and linear mixed-effects models.ResultsOver 5 years, the number of transfusion technicians increased by 72%, transfusion record scores improved by 34.6%, and per capita blood use decreased by 46.9%. However, blood use in low-complexity surgeries increased by an abnormal 200%. Tertiary hospitals showed higher blood use but better documentation than secondary hospitals. Regression analysis revealed that technician density (β = −0.280) and transfusion record score (β = −0.202) were negatively associated with blood use, whereas surgical complexity was positively associated with it. Hospital grade and type also significantly influenced outcomes.ConclusionEfficiency in blood utilisation is more strongly influenced by process standardisation and human resources than by hospital level or type alone. Rather than rigid indicators, policy incentives should emphasise precision transfusion strategies and dynamic quality management to align resource use with clinical need and support sustainable blood management systems.